Physicochemical Parameters and Bioactive Compounds of Strawberry Tree (Arbutus unedo L.) Honey - Pablo A. Ulloa; Miguel Maia; Amadeu F. Brigas (Journal of Chemistry)
Botanical origin, physicochemical properties (ash, colour, diastase activity, electrical conductivity (EC), hydroxymethylfurfural (HMF), moisture, optical rotation (OP), pH, reducing sugars, total acidity, total soluble solids, and water activity), bioactive compounds (BC), and antioxidant activity obtained from strawberry tree honey from South Portugal were investigated. Results showed that the pollen analysis and physicochemical parameters were found within to meet international honey specifications. Significant differences (P<0.05) in results of ash content, EC, HMF, OP and colour when were compared with analogous famous Italian honey (Sardinia island). For BC, total phenolic and total flavonoid content were 94.47 mg gallic acid/100 g and 5.33 mg quercetin/100 g, respectively. Concerning Portuguese honey, it was also found that radical scavenging activity (DPPH assay) was 43.46% and antioxidant activity was 18.85 mg ascorbic acid equivalent/100 g and 9.92 mg quercetin equivalent/100 g. These results confirmed that Portuguese strawberry tree honey has the highest antioxidant activity, when compared with other kinds of honey. This complete report demonstrates advantages and can help to promote consumption and shown their benefical properties (e.g., antioxidant); which will may increase the commercial value.